An attenuated herpesvirus vectored vaccine candidate induces T-cell responses against highly conserved porcine reproductive and respiratory syndrome virus M and NSP5 proteins that are unable to control infection - de Brito, Rory C. F.; Holtham, Kerry; Roser, Jessica; Saunders, Jack E.; Wezel, Yvonne; Henderson, Summer; Mauch, Thekla; Sanz-Bernardo, Beatriz; Frossard, Jean-Pierre; Bernard, Matthieu; Lean, Fabian Z. X.; Nunez, Alejandro; et al. (Frontiers in Immunology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) remains a leading cause of economic loss to pig farming worldwide. Existing commercial vaccines, all based on modified live or inactivated PRRSV, fail to provide effective immunity against highly diverse circulating strains of both PRRSV-1 and PRRSV-2. There is therefore an urgent need to develop more effective and broadly acting PRRSV vaccines. In the absence of neutralizing antibodies, T cells are thought to play a central role in controlling PRRSV infection. Herpesvirus-based vectors are a novel vaccine platform capable of inducing high levels of T cells against encoded heterologous antigens. The aim of this study was therefore to assess the immunogenicity and efficacy of an attenuated herpesvirus-based vector (bovine herpesvirus-4; BoHV-4) expressing a fusion protein comprised of two well-characterized PRRSV-1 T cell antigens (M and NSP5). Prime-boost immunization of pigs with BoHV-4 expressing the M and NSP5 fusion protein (vector designated BoHV-4-M-NSP5) induced strong IFN-γ responses as assessed by ELISpot assays of peripheral blood mononuclear cells (PBMC) stimulated with a pool of peptides representing PRRSV-1 M and NSP5. Responses were closely mirrored by spontaneous IFN-γ release from unstimulated cells albeit at lower levels. A lower frequency of M and NSP5 specific IFN-γ responding cells was induced following a single dose of the BoHV-4-M-NSP5 vector. Restimulation with M and NSP5 peptides from PRRSV-2 demonstrated a high level of cross-reactivity. Vaccination with BoHV-4-M-NSP5 did not have any effect on viral loads in either the blood or lungs following challenge with two heterologous PRRSV-1 strains. However, BoHV-4-M-NSP5 prime-boost vaccination showed a marked trend toward reduced lung pathology following PRRSV-1 challenge. The limited effect of T cells on PRRSV-1 viral load was further examined by analysis of local and circulating T cell responses using intracellular cytokine staining and T cell proliferation assays. Results from this study suggest that the vaccine-primed T cell responses may help in control of PRRSV-1 associated tissue damage, but had a minimal, if any, effect on controlling PRRSV-1 viral loads. Together, these results indicate that future efforts to develop effective PRRSV vaccines should focus on achieving a balanced T cell and antibody response.